2018
DOI: 10.4014/jmb.1807.07033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response and Enhanced Intestinal Adhesion Ability of Lactobacillus rhamnosus GG after Acid Stress

Abstract: Lactobacillus rhamnosus GG (LGG) is a probiotic commonly used in fermented dairy products. In this study, RNA-sequencing was performed to unravel the effects of acid stress on LGG. The transcriptomic data revealed that the exposure of LGG to acid at pH 4.5 (resembling the final pH of fermented dairy products) for 1 h or 24 h provoked a stringent-type transcriptomic response wherein stress response-and glycolysis-related genes were upregulated, whereas genes involved in gluconeogenesis, amino acid metabolism, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…On the other hand, the capacity of Lactobacillus casei Shirota to adhere to the mucus was not decreased after freeze‐drying (Du Toit et al ., ). Interestingly, the spaCBA and spaFED gene cluster were recently shown to be upregulated after exposure to an acid medium resulting in a higher expression of pili on the surface of Lactobacillus rhamnosus GG (Bang et al ., ). This indicates that adherence to intestinal cells could be increased after exposure to an acidic conditions, like the stomach, indicating that pili might rapidly re‐emerge in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the capacity of Lactobacillus casei Shirota to adhere to the mucus was not decreased after freeze‐drying (Du Toit et al ., ). Interestingly, the spaCBA and spaFED gene cluster were recently shown to be upregulated after exposure to an acid medium resulting in a higher expression of pili on the surface of Lactobacillus rhamnosus GG (Bang et al ., ). This indicates that adherence to intestinal cells could be increased after exposure to an acidic conditions, like the stomach, indicating that pili might rapidly re‐emerge in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…Several genes involved in carbohydrate metabolism, especially transglycosylase genes, were up-regulated. Previous studies have reported that alteration of carbohydrate metabolism under acid stress conditions enables bacteria to better resist acid stress by increasing their energy supply 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid easily diffuses into the cytoplasm and dissociates into protons and anions, disrupts the intracellular pH, and impairs normal cellular function 31 . During fermentation, Lactobacillus transports lactic acid outside the cell as lactate ions via an electrogenic proton-lactate symporter 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This strain-dependent effect of Resveratrol is also illustrated in our study, with an increased biofilm formation by some Resveratrol-treated Lacticaseibacillus strains, including the L. paracasei ATCC334 strain, whereas a decreased biofilm formation is observed for some others Resveratrol-treated strains of the same group, including three L. paracasei strains. Beyond Resveratrol effects on physico-chemical properties of bacterial cell surface, we could not exclude that Resveratrol might act indirectly by, for instance, modifying the production of exopolysaccharides (EPS) substances or by changing the expression profile of cell surface proteins (adhesins, pili) that can be, both of them, involved in adhesion processes [ 58 , 59 , 60 , 61 ]. A study using L. acidophilus NCFM strain has demonstrated that a 100 µg/mL dose of Resveratrol (corresponding to about 438 µM) stimulates adhesion to intestinal epithelial cells and increases the abundance of some proteins at bacterial surface (pyruvate kinase, 50S ribosomal protein L7/L12, elongation factor P) while decreasing some others (adenylosuccinate synthetase, and 6-phosphofructokinase) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%